TRENDS IN CHILD MARRIAGE IN AKURE METROPOLIS, ONDO STATE, NIGERIA - Justina Olufunke; Gbemisola Hannah ADEOBA (International Studies Journal, 2022)
Child-marriage is a global problem that cuts across countries, religions, and ethnicities. Despite national laws and international protocols forbidding early marriage, this phenomenon is still widespread in many developing countries with a high prevalence in sub-Saharan Africa, especially in Nigeria, where it still persists. This study examines the trends in child-marriage in Akure metropolis, Ondo State, Nigeria, and the strategies for its prevention. Using Key Informants Interviews (IKIs), the study shows the common trend is that of the parents or relatives promising in marriage their under-aged daughters or girls to their family-friends, neighbours, or associates as young wives to repay debts, settle disputes, or seal social, economic, and political alliances in order to deepen friendly relations with associates. The study concludes that the imposition of a marriage partner on under-aged daughters and girls who are in no way ready for married life, and who early-marriage can deprive of freedom, opportunities for personal development, and other human rights including health and well-being, education, and participation in civic life, appears to nullify the goals of the child’s core protections guaranteed by the Convention on the Rights of the Child. To tackle this challenging phenomenon, concerted efforts to formulate, and implement relevant policies and strategies are urgently needed. Actions to fulfill or restore the rights of those already married should go hand in hand with preventive actions to ensure that all of the intervention-mechanisms are available to both married and unmarried girls.